Effect of COVID-19 pandemic lockdowns on planned cancer surgery for 15 tumour types in 61 countries: an international, prospective, cohort study. Issue 11 (November 2021) - ,; Glasbey, James; Ademuyiwa, Adesoji; Adisa, Adewale; AlAmeer, Ehab; Arnaud, Alexis P; Ayasra, Faris; Azevedo, JosÃ©; Minaya-Bravo, Ana; Costas-Chavarri, Ainhoa; Edwards, John; Elhadi, Muhammed; et al.
Summary: Background: Surgery is the main modality of cure for solid cancers and was prioritised to continue during COVID-19 outbreaks. This study aimed to identify immediate areas for system strengthening by comparing the delivery of elective cancer surgery during the COVID-19 pandemic in periods of lockdown versus light restriction. Methods: This international, prospective, cohort study enrolled 20â€ˆ006 adult (â‰¥18 years) patients from 466 hospitals in 61 countries with 15 cancer types, who had a decision for curative surgery during the COVID-19 pandemic and were followed up until the point of surgery or cessation of follow-up (Aug 31, 2020). Average national Oxford COVID-19 Stringency Index scores were calculated to define the government response to COVID-19 for each patient for the period they awaited surgery, and classified into light restrictions (index <20), moderate lockdowns (20â€"60), and full lockdowns (>60). The primary outcome was the non-operation rate (defined as the proportion of patients who did not undergo planned surgery). Cox proportional-hazards regression models were used to explore the associations between lockdowns and non-operation. Intervals from diagnosis to surgery were compared across COVID-19 government response index groups. This study was registered at ClinicalTrials.gov, NCT04384926 . Findings: Of eligible patients awaiting surgery, 2003 (10Â·0%) of 20â€ˆ006 did not receive surgery after a median follow-up of 23 weeks (IQR 16â€"30), all of whom had a COVID-19-related reason given for non-operation. Light restrictions were associated with a 0Â·6% non-operation rate (26 of 4521), moderate lockdowns with a 5Â·5% rate (201 of 3646; adjusted hazard ratio [HR] 0Â·81, 95% CI 0Â·77â€"0Â·84; p<0Â·0001), and full lockdowns with a 15Â·0% rate (1775 of 11â€ˆ827; HR 0Â·51, 0Â·50â€"0Â·53; p<0Â·0001). In sensitivity analyses, including adjustment for SARS-CoV-2 case notification rates, moderate lockdowns (HR 0Â·84, 95% CI 0Â·80â€"0Â·88; p<0Â·001), and full lockdowns (0Â·57, 0Â·54â€"0Â·60; p<0Â·001), remained independently associated with non-operation. Surgery beyond 12 weeks from diagnosis in patients without neoadjuvant therapy increased during lockdowns (374 [9Â·1%] of 4521 in light restrictions, 317 [10Â·4%] of 3646 in moderate lockdowns, 2001 [23Â·8%] of 11â€ˆ827 in full lockdowns), although there were no differences in resectability rates observed with longer delays. Interpretation: Cancer surgery systems worldwide were fragile to lockdowns, with one in seven patients who were in regions with full lockdowns not undergoing planned surgery and experiencing longer preoperative delays. Although short-term oncological outcomes were not compromised in those selected for surgery, delays and non-operations might lead to long-term reductions in survival. During current and future periods of societal restriction, the resilience of elective surgery systems requires strengthening, which might include protected elective surgical pathways and long-term investment in surge capacity for acute care during public health emergencies to protect elective staff and services. Funding: National Institute for Health Research Global Health Research Unit, Association of Coloproctology of Great Britain and Ireland, Bowel and Cancer Research, Bowel Disease Research Foundation, Association of Upper Gastrointestinal Surgeons, British Association of Surgical Oncology, British Gynaecological Cancer Society, European Society of Coloproctology, Medtronic, Sarcoma UK, The Urology Foundation, Vascular Society for Great Britain and Ireland, and Yorkshire Cancer Research.